Heritage assets in Malaysia: perspectives of Malaysian government agencies / Mohamad Hafiz Rosli … [et al.] - Rosli, Mohamad Hafiz; Hasbolah, Farhana; Yahya, Nur Fauzana; Kamaluddin, Amrizah (Faculty of Accountancy, 2019)
The accounting of heritage assets (HA) has become an important discussion topic consistent with the implementation of the Malaysian Public Sector Accounting Standards (MPSAS). Among the issues were recognition, measurement as well as the information needed to be disclosed. This study discovers how the government agencies respond to the accounting for HA particularly the valuation and disclosure aspect of it. This study adopted a semi-structured face to face interviews for data collection. Two government departments were identified as these departments have unique, special and rare assets as compared to other government departments. Their perspective towards accounting for HA reveals that they are ready for HA valuation and in the process to recognize and value their HA. On top of that, policymaker needs to provide clear accounting guidelines and strengthen the recognition and measurement process as well as the disclosure part of HA. Other factors such as lack of technical knowledge and understanding among the factors could be distorting the accounting process. The agencies perceived that recognizing HA and disclosing it is important for public knowledge and exposure towards the national valuable HA. The finding of this study contributes to the existing literature on HA and could be the guideline to the policymakers and preparers of public sector financial statements.